2013
DOI: 10.1111/ajt.12451
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender and Gender Match on Mortality in Pediatric Heart Transplantation

Abstract: The effect of organ–recipient gender match on pediatric heart transplant mortality is unknown. We analyzed the effects of gender and donor–recipient gender matching. Based on Organ Procurement and Transplant Network data, we performed a historical cohort study in a population of 3630 heart transplant recipients less than 18 years old. We compared unadjusted and adjusted mortality by recipient gender, donor gender and between gender‐matched and gender‐mismatched recipients. Female recipients had decreased survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Female gender was also a risk factor for five‐yr adjusted mortality. These observations confirm findings of prior adult and pediatric studies about the small but repeatedly observed survival disadvantage and higher risk of severe rejection in female recipients that cannot be thoroughly explained by size mismatching.…”
Section: Discussionsupporting
confidence: 89%
“…Female gender was also a risk factor for five‐yr adjusted mortality. These observations confirm findings of prior adult and pediatric studies about the small but repeatedly observed survival disadvantage and higher risk of severe rejection in female recipients that cannot be thoroughly explained by size mismatching.…”
Section: Discussionsupporting
confidence: 89%
“…However, a recent report from Tosi et al . looking at the effect of gender and gender mismatch on pediatric heart transplant outcomes found that while female recipients had overall worse outcomes, the donor gender itself did not have any significant effect on survival for male or female recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Providers will evaluate immunocompatibility, potential implications of sex matching, recipient characteristics such as pulmonary hypertension and the donor‐recipient size match. In pediatrics, unlike in adult heart transplantation, sex mismatch has not been found to significantly affect outcomes . There are also emerging data suggesting that the historical preference for larger donors for recipients with elevated pulmonary pressures may not be justified .…”
Section: Introductionmentioning
confidence: 99%